Building Mobile Applications Using Kendo UI Mobile and ASP.NET Web API : Get Started with Kendo UI Mobile and Learn How to Integrate It with HTTP-Based Services Built Using ASP.NET Web API /: Get Started with Kendo UI Mobile and Learn How to Integrate It with HTTP-Based Services Built Using ASP.NET Web API. (2013) - Unknown
No abstract available